Strategi Hubungan Masyarakat dalam Meningkatkan Partisipasi Aktif Wali Murid di MTs Ihyaul Ulum Bluri Solokuro Lamongan - Yogi Kurniawan Prayetno (Mudir : Jurnal Manajemen Pendidikan, 2022)
The public relations strategy in increasing the active participation of parents is one way to foster and develop a harmonious relationship between the school and the parents. MTs. Ihyaul Ulum Bluri Solokuro Lamongan is one of the educational institutions built through public relations activities, where the use of public relations activities advances the quality of the educational institution. Thus, schools realize the importance of parental support in order to advance and develop their education. This was done by the school so that more parents were interested in sending their children to the school and so that the participation of parents with the school could increase, so this research was carried out. This study aims to determine: first, how is the public relations strategy in increasing the active participation of parents?; second, about the factors supporting and inhibiting the public relations strategy in increasing the active participation of parents? This type of research includes qualitative research, by searching for data and then analyzing it using descriptive methods. The data sought using interview, observation and documentation techniques. The results of this study indicate that the public relations strategy in MTs. Ihyaul Ulum Bluri Solokuro Lamongan is an effort to realize the role of schools in providing quality education. In meeting these needs, the public relations strategy is carried out systematically. Starting from planning activities, public relations in increasing the active participation of parents who are carried out based on work meetings at the beginning of each semester, this refers to an analysis of the needs and desires of the internal and external community. Then the implementation of public relations is carried out according to a predetermined schedule, as for the types of active parental participation that have been carried out, namely: 1) Energy or physical participation, 2) Ideas or thoughts participation and 3) Fund participation. Then, program evaluation. In implementing the evaluation, MTs. Ihyaul Ulum Bluri holds a meeting every six months, namely before the odd semester, before the even semester and before the increase. The supporting factors in the field of public relations to carry out the program are: enthusiastic parents of students in supporting school activities and also school residents who have a high sense of belonging and enthusiasm for the progress of the school and strong brotherly bonds. Meanwhile, the inhibiting factor is that the parents do not understand the digital world, which is the biggest opportunity for the public relations field to run its program and the lack of funding as well as the lack of professionalism of public relations practitioners. As for the results of this study, it is recommended that in the future public relations practitioners are more optimal in applying the competence and code of ethics of public relations properly to make it easier for educational institutions to coordinate, plan, negotiate and build good relations between educational institutions and guardians of students.